ONCOEPIDEMIOLOGY OF CUTANEOUS MELANOMA IN THE CHERNIGIV REGION AND PROBLEMS OF ITS EARLY DIAGNOSIS - Alevros, Олександр; Роletai, Вячеслав (Biota. Human. Technology, 2023)
Purpose. To investigate the main onco-epidemiological indicators of malignant melanocytic skin neoplasms in the city of Chernihiv and the Chernihiv region, to analyze the methods of their early diagnosis, to determine their dynamics in the period from 2014 to 2021, to analyze the effectiveness of preventive, diagnostic and treatment measures in medical institutions of the Chernihiv region according to indicators 5- annual survival of patients diagnosed with melanoma of the skin. Methodology. Statistical data of the Chernihiv Medical Center of Modern Oncology and the National Cancer Registry of Ukraine for the period from 2014 to 2021 were analyzed for the main indicators of skin melanoma: morbidity, mortality and 5-year survival; an analysis of the scientific literature on early and differential diagnosis of cutaneous melanoma was carried out. Scientific novelty The onco-epidemiological indicators of melanoma of the skin in the Chernihiv region for the period from 2014 to 2021 were analyzed, and the effectiveness of preventive, diagnostic and treatment measures in medical institutions of the Chernihiv region was evaluated based on the 5-year survival rates of patients diagnosed with melanoma. Conclusions. The rates of cutaneous melanoma morbidity and mortality from this disease in the city of Chernihiv and the Chernihiv region in the period from 2014 to 2021 have no tendency to increase, but were 1.4 times higher than the rates for Ukraine. The 5-year survival rate tends to increase, which may indicate the gradual improvement of methods of prevention, diagnosis and treatment of cutaneous melanoma in medical institutions of the Chernihiv region. Most often, the second stage of melanoma is diagnosed (half of all cases), which indicates an insufficient level of cancer awareness among the population. The defined typical dermatoscopic signs of cutaneous melanoma and its diagnostic algorithms should be known to primary care physicians, and the population, especially those with a burdensome medical history and the presence of pre-melanoma neoplasms, should be sufficiently aware of the need to monitor for changes in the neoplasm and contact specialists in a timely manner.